What characterises mathematical conversations in a Norwegian kindergarten? - Fosse, Trude (NOMAD Nordic Studies in Mathematics Education, 2016)
This paper presents a study of young children’s mathematical conversations in a Norwegian kindergarten and provides examples to illustrate some of their characteristics. Using points made in previous research about conversations and mathematics, an analysis of an interaction involving a group of children who are putting a toy together exemplifies what can and what cannot be considered a mathematical conversation. For a conversation to be considered mathematical, it is suggested that it must include not only references to mathematics, but also specific structural elements in the conversation, as well as valuing participants’ contributions and encouraging participants to reflect on the mathematical theme, thereby promoting learning.